The Impact of Supervision Compensation Work Team and Career Advancement Opportunities on Nurse Job Satisfaction at Hospital X 2024: Pengaruh Supervisi Insentif Tim Kerja dan Peluang Pengembangan karir Pada Kepuasan Kerja Perawat di Rumah Sakit X 2024 - Nawangwulan, Kurniati; Zulaika; Yusfik, Yusnita (Universitas Mohammad Husni Thamrin, 2025)
Nurses are Human Resources (HR) who hold an important role in the progress of the organization in the hospital. In carrying out services, nurses have a crucial role, both in the implementation of medical procedures, monitoring the patient's condition, and monitoring their development during treatment. The purpose of this study is to find out the influence of Supervision, Incentives, Work Team, and Career Development Opportunities on Nurses' Job Satisfaction. The research approach is using a cross sectional survey. The research will be carried out in December 2024. The population and sample in this study are 52 nurses who are on duty in the inpatient room of Hospital X with accident techniques. The research instrument used a questionnaire with a linkert scale Data analysis included validation, reliability tests and analysis of the Chi Square test or Fisher Test. The results of this study show that there is a significant influence between supervision, intensive, work team and career development opportunities with nurses' job satisfaction,Recommendations to increase supervision, intensive, work teams and career development opportunities for nurses in hospitals. Keywords: Supervision, Incentives, Work Team, Career Development Opportunities, Nurse Job Satisfaction